Vaccine effectiveness of two-dose BNT162b2 against symptomatic and severe COVID-19 among adolescents in Brazil and Scotland over time: a test-negative case-control study - Florentino, Pilar T. V. (2022)
Research and Innovation (Medical Research Council). Scottish Government. Health Data Research UK. BREATHE Hub, Fiocruz. Fazer o Bem Faz Bem programme. Brazilian National Research Council. Wellcome Trust.